Development and evaluation of Desvenlafaxine loaded PLGA-chitosan nanoparticles for brain delivery - Gui-Feng Tong; Nan Qin; Li-Wei Sun (Saudi Pharmaceutical Journal)
Depression is a debilitating psychiatric condition that remains the second most common cause of disability worldwide. Currently, depression affects more than 4 per cent of the world’s population. Most of the drugs intended for clinical management of depression augment the availability of neurotransmitters at the synapse by inhibiting their neuronal reuptake. However, the therapeutic efficacy of antidepressants is often compromised as they are unable to reach brain by the conventional routes of administration. The purpose of the present study was to reconnoiter the potential of mucoadhesive PLGA-chitosan nanoparticles for the delivery of encapsulated Desvenlafaxine to the brain by nose to brain delivery route for superior pharmacokinetic and pharmacodynamic profile of Desvenlafaxine. Desvenlafaxine loaded PLGA-chitosan nanoparticles were prepared by solvent emulsion evaporation technique and optimized for various physiochemical characteristics. The antidepressant efficacy of optimized Desvenlafaxine was evaluated in various rodent depression models together with the biochemical estimation of monoamines in their brain. Further, the levels of Desvenlafaxine in brain and blood plasma were determined at various time intervals for calculation of different pharmacokinetic parameters. The optimized Desvenlafaxine loaded PLGA-chitosan nanoparticles (∼172 nm/+35 mV) on intranasal administration significantly reduced the symptoms of depression and enhanced the level of monoamines in the brain in comparison with orally administered Desvenlafaxine. Nose to brain delivery of Desvenlafaxine PLGA-chitosan nanoparticles also enhanced the pharmacokinetic profile of Desvenlafaxine in brain together with their brain/blood ratio at different time points. Thus, intranasal mucoadhesive Desvenlafaxine PLGA-chitosan nanoparticles could be potentially used for the treatment of depression.